PENGARUH LINGKUNGAN KELUARGA TERHADAP PERILAKU BULLYING PESERTA DIDIK KELAS VII DI SMP NEGERI 16 PADANG - Mutia Sri Wahyuni; Mori Dianto; Suryadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the less than optimal efforts of guidance and counseling teachers to improve the emotional development of students who use gadgets. The purpose of this study is to describe the efforts of guidance and counseling teachers to improve the emotional development of students who use gadgets reviewed from: 1) self-awareness, 2) emotional management, and 3) Empathy. This study uses a qualitative approach with descriptive data. The results of the study indicate that guidance and counseling teachers have a strategic role in guiding students to be able to develop self-awareness, manage emotions, and build empathy. In the aspect of self-awareness, guidance and counseling teachers help students recognize their strengths and weaknesses through active communication and a supportive approach. In the aspect of emotional management, guidance and counseling teachers create a positive emotional atmosphere through counseling services tailored to the character of students, while in the aspect of empathy, guidance and counseling teachers show concern and readiness in responding to students' emotional problems by upholding professional ethics. These efforts demonstrate the importance of the role of guidance and counseling teachers in accompanying the emotional development of students in the era of increasingly intensive gadget use.